Cardio‐pulmonary resuscitation of brain‐dead organ donors: a literature review and suggestions for practice. (6th July 2015) - Dalle Ave, Anne L.; Gardiner, Dale; Shaw, David M.
Summary: "Organ preserving cardiopulmonary resuscitation (OP‐CPR)" is defined as the use of CPR in cases of cardiac arrest to preserve organs for transplantation, rather than to revive the patient. Is it ethical to provide OP‐CPR in a brain‐dead organ donor to save organs that would otherwise be lost? To answer this question, we review the literature on brain‐dead organ donors, conduct an ethical analysis, and make recommendations. We conclude that OP‐CPR can benefit patients and families by fulfilling the wish to donate. However, it is an aggressive procedure that can cause physical damage to patients, and risks psychological harm to families and healthcare professionals. In a brain‐dead organ donor, OP‐CPR is acceptable without specific informed consent to OP‐CPR, although advance discussion with next of kin regarding this possibility is strongly advised. In a patient where brain death is yet to be determined, but there is known wish for organ donation, OP‐CPR would only be acceptable with a specific informed consent from the next of kin. When futility of treatment has not been established or it is as yet unknown if the patient wished to be an organ donor then OP‐CPR should be prohibited, in order to avoid any conflict of interest.